Saluran Pemasaran Biji Jambu Mete (Anacardium occidentale) Sebagai Hasil Hutan Bukan Kayu Hutan Kemasyarakatan Desa Gunung Silanu, Kabupaten Jeneponto - Nurhikmah Nurhikmah; Laswi Irmayanti; Adesna Fatrawana; Asiah Salatalohy (EnviroScienteae, 2020)
Non-timber forest product commodities in Gunung Silanu Village are cashew, turmeric, candlenut, coffee, cocoa, ginger, and galangal. Among these commodities, cashew and turmeric are the most developed commodities. However, this study is focused on the cashew (Anacardium occidantale). Cashew seed processing in Gunung Silanu Village only reaches into the drying stage, even though there was a peeling tool available. This condition makes farmers market their cashew seeds directly. There is a problem that frequently encountered in marketing cashew seeds, namely the unconstant price of cashew seeds. This certainly affects farmers' income. Therefore, a study related to marketing channels for cashew nuts in the village of Gunung Silanu to see the price level at each marketing institution is needed. The purposes of this study were to determine marketing channels, analyze marketing margins, and marketing efficiency levels of cashew nuts (Anacardium occidentale) was a non-timber forest product at community forestry in Gunung Silanu Village. The results showed that there were two marketing channels. The first marketing channels were from farmers to large traders in the village of Gunung Silanu then to large traders in Jeneponto Regency. The second marketing channels were from farmers to small traders and large traders in Gunung Silanu Village then to large traders in Jeneponto Regency. The marketing margin of the big traders in the first channel is 15.6% with an efficiency level of 0.48%, while in the second channel is 13.4% and 11.3% for small traders and big traders respectively, so the total marketing margin is 23.3 % with an efficiency level of 0.48%. The most efficient channel is a channel with small costs, large margins, and a short marketing channel which is the first channel.